Faktor-faktor yang mempengaruhi kepatuhan diet pasien hemodialisis - Fery Lusviana Widiany (Jurnal Gizi Klinik Indonesia, 2017)
Background: Riskesdas 2013 data shows the prevalence of chronic kidney disease in Central Java and Yogyakarta 0.3%, which is higher than the average prevalence across Indonesia which is only 0.2%. The results of the author’s study previously showed that the intake of energy, protein, sodium hemodialysis patients on average are not sufficient, while the average fluid intake exceeds the dietary recommendation. There are several factors that can affect dietary compliance of the hemodialysis patients, such as knowledge, family support, attitudes, and behavior.Objective: To examine the factors that affect dietary compliance of the hemodialysis patients.Method: This is an observational study with cross-sectional design, conducted in the hemodialysis unit of Dr. Soeradji Tirtonegoro Hospital, Klaten on March - October 2016, involving 60 respondents. The dependent variable is dietary compliance, while the independent variables are knowledge, family support, attitudes, and behavior. Data were analyzed using univariate and bivariate with Chi-Square test.Results: Chi-Square test results of knowledge with dietary compliance showed the p-value = 0.027; family support with dietary compliance showed the p-value = 0.045; attitude with dietary compliance showed the p-value = 0.045; and behavior with dietary compliance showed the p-value = 0.002.Conclusion: Knowledge, family support, attitude, and behavior affect dietary compliance of the hemodialysis patients.